Resolvin D2 Induces Resolution of Periapical Inflammation and Promotes Healing of Periapical Lesions in Rat Periapical Periodontitis - Siddiqui, Yasir Dilshad; Omori, Kazuhiro; Ito, Takashi; Yamashiro, Keisuke; Nakamura, Shin; Okamoto, Kentaro; Ono, Mitsuaki; Yamamoto, Tadashi; Van Dyke, Thomas E.; Takashiba, Shogo (Frontiers in Immunology, 2019)
Periapical periodontitis results from pulpal infection leading to pulpal necrosis and resorption of periapical bone. The current treatment is root canal therapy, which attempts to eliminate infection and necrotic tissue. But, in some cases periapical inflammation doesn’t resolve even after treatment. Resolvins are part of a large family of specialized pro-resolving lipid mediators that actively resolves inflammation signalling via specific receptors. Resolvin D2 (RvD2), a metabolite of docosahexaenoic acid (DHA), was tested as an intracanal medicament in rats in vivo. Mechanism was evaluated in rat primary dental pulp cells (DPCs) in vitro. The results demonstrate that RvD2 reduces inflammatory cell infiltrate, bacterial load and periapical lesion size, and fosters pulp like tissue regeneration and root apex calcification. RvD2 enhanced expression of its receptor, GPR18, and dentin matrix acidic phosphoprotein 1 (DMP1) in vivo and in vitro. Moreover, RvD2 induces phosphorylation of Stat3 transcription factor in dental pulp cells. We conclude that intracanal treatment with RvD2 resolves inflammation and increases efficiency of bacterial clearance promoting root apex calcification and healing of periapical bone lesions. The data suggest that RvD2 induced active resolution of inflammation is suitable for healing of periapical lesions, with pulp-like tissue regeneration after root canal infection.